Plato on the Political Role of Poetry: the Expulsion of the Traditional Poets and the Reform of Poetry (2016)
(Eng) Plato offers two criticisms of imitative poetry in the Republic. In the first one, developed in books II and III, Plato seems to criticize poetry softly, banning only one part of imitative poetry. The second criticism, developed in book x , seems to establish a more drastic critique to imitative poetry that precludes the possibility of any kind of imitative poetry in the polis. Many different interpretations have been proposed in order to account for this apparent clash. I will defend Tate’s classical interpretation, according to which no clash exists because Plato distinguishes two kinds of imitations, and he remains consistent in preserving one and banishing the other.